2018
DOI: 10.12998/wjcc.v6.i6.139
|View full text |Cite
|
Sign up to set email alerts
|

Posterobasal left ventricular aneurysm after myocardial infarction with normal coronary arteries: Case-report

Abstract: We present a case of a 64-year-old woman with signs of debilitating condition including anginal chest pain, exertional dyspnea, and depression. The patient had previously suffered from a myocardial infarction after a loss of a close family member. Workup showed a posterobasal left ventricular aneurysm and moderate to severe mitral regurgitation in the absence of coronary atherosclerosis. Routine ultrasonography revealed abdominal aortic aneurysm and intraabdominal aortic deviation. The patient was immediately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The proposed mechanisms for MINOCA include coronary vasospasm, coronary thrombosis in situ or embolization from distal source with spontaneous lysis, cocaine abuse, viral myocarditis, aortic dissection, hypercoagulable states, autoimmune vasculitis and carbon monoxide poisoning [6]. MINOCA has been rarely associated with the development of an LV aneurysm [7]. In the case we are presenting the careful reading of the ECGs and the negative coronary angiography was the clue for the final diagnosis.…”
Section: Discussionmentioning
confidence: 90%
“…The proposed mechanisms for MINOCA include coronary vasospasm, coronary thrombosis in situ or embolization from distal source with spontaneous lysis, cocaine abuse, viral myocarditis, aortic dissection, hypercoagulable states, autoimmune vasculitis and carbon monoxide poisoning [6]. MINOCA has been rarely associated with the development of an LV aneurysm [7]. In the case we are presenting the careful reading of the ECGs and the negative coronary angiography was the clue for the final diagnosis.…”
Section: Discussionmentioning
confidence: 90%
“…Only case reports exist to address this conundrum. The therapeutic strategies vary from optimal medical treatment [ 9 ] to left ventricular reconstruction [ 7 , 8 ] to epicardial ablation [ 6 ]. The indication for surgery in our patient series was consistent with Li B’s [ 7 ] and Takaseya’s reports [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown better outcomes than their acute myocardial infarction-obstructive coronary artery disease counterparts [ 13 , 35 , 36 ]. However, there were only case reports reporting the prognosis of patients with MINOCA and left ventricular aneurysm, with different management strategies implemented [ 6 9 ]. In our series, surgical indications for patients without obstructive coronary arteries were accordant with those with obstructive coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation